Anthelmintic Potential of Annona muricata Leaf Extract against Parasitic Nematode Haemonchus contortus - Pratiwi, Baiq Yulia Hasni; Novitarini, Novitarini (Jurnal Pijar Mipa, 2025)
Gastrointestinal infections caused by the parasitic worm Haemoncus contortus are the main cause of economic losses in the agricultural sector. H. contortus causes small ruminants such as goats to experience acute anemia and diarrhea, weight loss, decreased productivity, and eventually mortality, which impacts economic losses. Synthetic antiparasitics have been used extensively around the world to combat haemonchosis. However, the emergence of resistance to anthelmintics, accompanied by the unavailability of an effective vaccine, results in difficulties in controlling this disease. Because of the high cost of treatment and the emergence of resistance and toxicity due to the residue of antiparasitic drugs, it is necessary to develop natural anthelmintics that are easy to obtain, economical, and have minimal risk. This study aims to determine the anthelmintic effect of Annona muricata leaf extract on mice infected with H. contortus larvae. First, an in vitro study was conducted to see if the soursop leaf extract from Lombok would show a different effect from the previous research. In the in vivo test, the impact of A. muricata leaf extract was measured from the number of H. contortus eggs found in the feces and the percent reduction of adult worms collected from mice's stomachs. The result shows that the higher the concentration of soursop leaf extract, the higher the inhibition effect on larvae motility. The combination of A. muricata and albendazole had the strongest antiparasitic effect, shown by the lowest amount of eggs in feces and the highest reduction of adult worms in the stomach. However, administering A. muricata leaf extract can also reduce the number of eggs and adult worms in the stomach. Therefore, it can be concluded that A. muricata is a potential anthelmintic candidate for overcoming the H. contortus infection.